2019
DOI: 10.1007/s40843-019-1217-4
|View full text |Cite|
|
Sign up to set email alerts
|

Bio-inspired anisotropic polymeric heart valves exhibiting valve-like mechanical and hemodynamic behavior

Abstract: Native heart valve leaflets with layered fibrous structures show anisotropic characteristics, allowing them to withstand complex mechanical loading for long-term cardiac cycles. Herein, two types of silk fibroin (SF) fiber membranes with anisotropic (ASF) and isotropic (ISF) properties were prepared by electrospinning, and were further combined with poly(ethylene glycol) diacrylate (PEGDA) hydrogels to serve as polymeric heart valve (PHV) substitutes (PEGDA-ASF and PEGDA-ISF). The uniaxial tensile tests showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Textile fabric leaflets have faced criticisms because of their increasing rate of biofouling, bacterial infection, thrombogenesis, and extreme regurgitation flow through the pores; [ 79 ] to mitigate the complications mentioned above, the textile materials were coated with poly (ethylene glycol) diacrylate (PEGDA) (Figure 6). [ 79,143 ] In one experiment, the polyester–nylon knitted fabric was wrapped around a stent and immersed in PEGDA solution to crosslink the polymers. [ 79 ] SEM image revealed that PEGDA had covered the surface of the fabric and filled the pores.…”
Section: Materials Used For Thvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Textile fabric leaflets have faced criticisms because of their increasing rate of biofouling, bacterial infection, thrombogenesis, and extreme regurgitation flow through the pores; [ 79 ] to mitigate the complications mentioned above, the textile materials were coated with poly (ethylene glycol) diacrylate (PEGDA) (Figure 6). [ 79,143 ] In one experiment, the polyester–nylon knitted fabric was wrapped around a stent and immersed in PEGDA solution to crosslink the polymers. [ 79 ] SEM image revealed that PEGDA had covered the surface of the fabric and filled the pores.…”
Section: Materials Used For Thvsmentioning
confidence: 99%
“…In another experiment, anisotropic silk fiber membranes coated with PEGDA had a 10 MPa elastic modulus along the fiber direction and 3.5 MPa in the transverse direction. [ 143 ] PEGDA‐coated silk fiber membranes were made into three leaflets and sutured together around a stent. From an in vitro study, this valve showed a large EOA (2.6 cm 2 ) but high RF (20%).…”
Section: Materials Used For Thvsmentioning
confidence: 99%
“…With the rapid development of material science, polymeric aortic valves are considered to be a competitive candidate for the aortic valve prosthesis that could eliminate shortcomings of the existing artificial heart valves. 2,3,20,46,[69][70][71][72][73][74][75][76][77][78] Researchers have been trying to develop ideal polymeric heart valve for decades. Trace back to the 1960s, the first polymeric heart valve has been implanted into the human body.…”
Section: Biomimetic Heart Valvementioning
confidence: 99%
“…Another example takes the anisotropic properties of native valves into consideration. Guo et al 69 reported a bioinspired polymeric fabricated heart valve by assembling electrospinning silk fibroin membranes with PEDGA hydrogel. In this study, two types of silk fibroin membranes -isotropic silk fibroin (ISF) membrane and directional aligned silk fibroin (DSF) membrane -were prepared with a baffle receiver and a rotating cylindrical receiver, respectively.…”
Section: Fiber Reinforced Matrixmentioning
confidence: 99%
“…However, the problem of microbial invasion caused by the weak integration between the hydrogel and wound, and the wound infection caused by the bacterial incubated in moist wound environment urgently need to be addressed [13,22,30]. In recent years, most solutions are based on hydrogel as the carrier to deliver antibacterial or silver nanoparticles [31][32][33]. However, inadequate stewardship of antibiotics can lead to antibiotics resistance, and the safety of silver ions is not clear [4,34].…”
Section: Introductionmentioning
confidence: 99%